The Effectiveness and Safety of Fluoroquinolone-Containing Regimen as a First-Line Treatment for Drug-Sensitive Pulmonary Tuberculosis: A Systematic Review and Meta-Analysis. - Hyun Woo Lee; Jung Kyu Lee; Eunyoung Kim; Jae-Joon Yim; Chang-Hoon Lee (PLoS ONE)
Background Fluoroquinolone is recommended as a pivotal antituberculous agent for treating multi-drug-resistant pulmonary tuberculosis. However, its effectiveness as first-line treatment remains controversial. The present study was conducted to validate the fluoroquinolone-containing regimen for drug-sensitive pulmonary tuberculosis. Methods We searched MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials until June 5, 2015. Randomized controlled trials (RCTs) that compared antituberculous regimens containing fluoroquinolone with the standard regimen were included. Results Eleven RCTs that included 6,334 patients were selected. Fluoroquinolone-containing regimens had a higher rate of sputum culture conversion at 2 months of treatment (M-H fixed odds ratio [OR], 1.36; 95% confidence interval [CI], 1.20-1.54). However, the outcomes were less favorable (M-H fixed OR, 0.69; 95% CI, 0.59-0.82) and the associated total adverse events were more frequent (M-H fixed OR, 1.84; 95% CI, 1.46-2.31) in the fluoroquinolone-containing regimen group, without a significant heterogeneity according to treatment duration. Treatment with the fluoroquinolone-containing regimen for 4 months showed a higher relapse rate. Conclusions Despite a higher culture conversion rate at 2 months of treatment, the fluoroquinolone-containing regimen had limitations, including less favorable outcomes and more adverse events, as the first-line therapy for drug-sensitive pulmonary tuberculosis.